Determinants of Utilization of COVID-19 Vaccination Services for Pregnant Women - Astutik, Risa Septi; Sriatmi, Ayun; Fatmasari, Eka Yunila (Preventia: The Indonesian Journal of Public Health, 2024)
The COVID-19 pandemic has caused an increase in the death rate of pregnant women. The government is taking preventive action by providing COVID-19 vaccination to pregnant women in accordance with the Circular Letter of the Ministry of Health of the Republic of Indonesia HK.02.01/I/2007/2021. Even though it has been carried out for 2 months, vaccination coverage is still low, especially in Temanggung Regency. This study aims to determine behavioral determinants in the use of COVID-19 vaccination services for pregnant women. This research uses an analytical survey method with a quantitative approach through a cross-sectional study. Taking 200 samples using the Accidental Sampling technique based on inclusion and exclusion criteria. Data was collected using a research questionnaire and then analyzed using the Spearman Rank test. The research results show that there is a weak relationship between employment status and perceived vulnerability and utilization of COVID-19 vaccination services among pregnant women. There is a fairly strong relationship between education level, perception of waiting time, and accessibility with the utilization of vaccination services for pregnant women. There is a strong relationship between attitudes, knowledge, availability of health facilities, availability of health workers, and ease of information with the use of COVID-19 vaccination services for pregnant women.